PENERAPAN DOKTRIN FAIR USE TERHADAP PEMANFAATAN HAK CIPTA PADA PLATFORM DIGITAL SEMASA COVID 19 DI INDONESIA - Rika Ratna Permata; Tasya Safiranita; Yuliana Utama; Reihan Ahmad Millaudy (Faculty of Law, Maranatha Christian University, 2021)
The Covid-19 pandemic has resulted in more people doing activities from home, so almost all activities are carried out online, including for educational activities. The problems on this research are how the comparison between fair use regulations in Indonesia and in the United States during the pre-Covid-19 pandemic? How the regulations of the doctrine of fair use to anticipate the occurrence of a new phenomenon regarding the use of copyright on digital platforms during and/or after the Covid-19 pandemic? The method used in writing this law is a normative juridical method. The results of the study conclude that Fair use rules in Indonesia already regulate that fair use will not harm the legitimate interests of creators but does not provide clear parameters regarding fair interests. While the Fair use Arrangements in the United States are regulated in 17 U.S. Code 107. In this regulation, there are 4 factors, namely: the purpose and character of the use, the nature of the copyrighted work, the quantity and importance of the material used, the effect of the use upon potential market or value of the copyrighted work. The Covid-19 pandemic gave rise to fair use cases that had never occurred before the outbreak of Covid-19, e.g. the case of The Internet Archive, it can be observed that there is an encouragement from the public to further relax copyright protection because of the Covid-19 pandemic resulting in the public interest having to be carried out rather than the creators and copyright holders.